2014
DOI: 10.1017/s1355617714000940
|View full text |Cite
|
Sign up to set email alerts
|

Facial Emotion Recognition Deficits following Moderate–Severe Traumatic Brain Injury (TBI): Re-examining the Valence Effect and the Role of Emotion Intensity

Abstract: Twenty-seven individuals with TBI and 28 matched control participants were tested on the Emotion Recognition Task (ERT). The TBI group was more impaired in overall emotion recognition, and less accurate recognizing negative emotions. However, examining the performance across the different intensities indicated that this difference was driven by some emotions (e.g., happiness) being much easier to recognize than others (e.g., fear and surprise). Our findings indicate that individuals with TBI have an overall de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
56
0
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 65 publications
15
56
0
14
Order By: Relevance
“…Regarding the KDEF, individuals with TBI performed significantly worse than NCs only on fear, disgust, and anger (three negatively valenced emotions) but not on surprise, sadness, happiness, or neutral faces. Although similar valence-based differences have been widely discussed before (Croker & McDonald, 2005; Green et al, 2004; Rosenberg, McDonald, Dethier, Kessels, & Westbrook, 2014), a study by Rosenberg using the ERT showed that individuals with TBI are equally impaired across all types of emotions when task difficulty is controlled across emotions (Rosenberg et al, 2015). Indeed, in our sample, the interaction found between group, emotion, and intensity offers a similar explanation.…”
Section: Discussionsupporting
confidence: 53%
“…Regarding the KDEF, individuals with TBI performed significantly worse than NCs only on fear, disgust, and anger (three negatively valenced emotions) but not on surprise, sadness, happiness, or neutral faces. Although similar valence-based differences have been widely discussed before (Croker & McDonald, 2005; Green et al, 2004; Rosenberg, McDonald, Dethier, Kessels, & Westbrook, 2014), a study by Rosenberg using the ERT showed that individuals with TBI are equally impaired across all types of emotions when task difficulty is controlled across emotions (Rosenberg et al, 2015). Indeed, in our sample, the interaction found between group, emotion, and intensity offers a similar explanation.…”
Section: Discussionsupporting
confidence: 53%
“…This indicated that participants with TBI were significantly underperforming HCs in a way that did not significantly vary across affect. Although several other tasks, both by our group and others, have previously reported group-by-affect interactions (Rigon, Turkstra, et al, 2016; Rosenberg, et al, 2015; Rosenberg, et al, 2014), it is possible that the different finding here is due to 1) the fact that the tasks used here included a higher number of trials for all types affect, thus providing a more complete assessment and 2) the use of mixed-effect modeling, which allows to account to the variance provided both by items and participants. Especially considering the fact that TBI research often works with relatively small samples, future research on affect recognition might benefit from the use of more complex statistical models, as well as larger sample sizes.…”
Section: Discussionmentioning
confidence: 47%
“…For Labeling, we tested the presence of a group-by-affect interaction as well as main effects of group and affect type. This was chosen based on previous reports that individuals with TBI are significantly more impaired when attempting to recognize specific emotion types, and negative emotions in particular (Rigon, Turkstra, et al, 2016; Rosenberg, et al, 2014). A likelihood-ratio test determined that the maximal random effect structure supported by the data (identified using a model simplification approach) included random intercepts for subject and item, as well as a random subject-by-affect type slope ( X 2 (1)=779.66, p <.001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further work is necessary to distinguish different patterns of social cognitive deficits associated with different neuropsychiatric disorders. Also, the relatively mild deficit in recognition of happiness is not specific to MS and is common finding across (Rosenberg et al 2014). Positive emotions other than recognition of happiness have been rarely used in neuropsychological research in neurological disorders.…”
Section: Discussionmentioning
confidence: 99%